Mimotopes selected by biopanning with high-titer HIV-neutralizing antibodies in plasma from Chinese slow progressors - Zhang,Xiaoli (2012)
OBJECTIVE: One approach to identifying HIV-1 vaccine candidates is to dissect the natural antiviral immune response in treatment-naïve individuals infected for over ten years, considered slow progressor patients (SPs). It is suspected that SP plasma has strongly neutralizing antibodies (NAb) targeting specific HIV viral epitopes. METHODS: NAbs levels of 11 HIV-1-infected SPs were detected by PBMC-based neutralization assays. To investigate SP NAb epitope, this study used a biopanning approach to obtain mimotopes of HIV-1 that were recognized by SP plasma NAbs. IgG was purified from hightiter NAb SP plasma, and used as the ligand for three rounds of biopanning to select HIV-specific mimotopes from a phage-displayed random peptide library. Double-antibody sandwich ELISA, competitive inhibition assays, and peptide sequence analysis were used to evaluate the characteristics of phage-borne mimotopes. RESULTS: SPs had significantly more plasma neutralizing activity than typical progressors (TPs) (p = 0.04). P2 and P9 plasma, which have highest-titer HIV-NAb, were selected as ligands for biopanning. After three rounds of biopanning, 48 phage clones were obtained, of which 22 clones were consistent with requirement, binding with HIV-1 positive plasma and unbinding with HIV-1 negative plasma. Compared with linear HIV-1 protein sequence and HIV-1 protein structure files, only 12 clones were possible linear mimotopes of NAbs. In addition, the C40 clone located in gp41 CHR was found to be a neutralizing epitope, which could inhibit pooled HIV-1 positive plasma reaction. CONCLUSION: Biopanning of serum IgG can yield mimotopes of HIV-1-related antigen epitopes. This methodology provides a basis for exploration into HIV-1-related antigen-antibody interactions and furthers NAb immunotherapy and vaccine design.